Alternative technique for clot retrieval: The "tip of the iceberg" technique. Issue 6 (December 2015) - Agid, Ronit; Power, Sarah
We present a variation of the classical technique of stent retriever thrombectomy which we found helpful in two patients presenting with acute stroke. CT angiography in both patients demonstrated thrombus within a middle cerebral artery M2 branch. In both cases the occluded artery was not visualized on DSA and only the proximal tip of the clot could be seen as a filling defect "hanging" into the parent artery reminiscent of a "tip of an iceberg". Rather than selectively catheterizing the occluded branch we placed the stent retriever in the patent parent artery crossing only the tip of the clot. In both cases one pass of the stent retriever was sufficient to retrieve the whole clot by its tip and reopen the occluded branch. We suggest trying this technique whenever the clot is seated in the proximal part of a secondary branch such as an M2 segment of middle cerebral artery. This "tip of the iceberg" technique prevents the need to selectively catheterize the occluded branch which, if difficult, can prolong procedural and ischemic time.